Elevated Zinc and Potassium Levels in Renal Calculi Indicate Distinct Pathophysiological Mechanisms in Urolithiasis - Maciej Jaromin; Marcin Cichocki; Tomasz Konecki; Piotr Kutwin; Waldemar Maniukiewicz; Piotr Wysocki; Magdalena Gajek; Małgorzata Iwona Szynkowska-Jóźwik; Dariusz Moczulski (Pathophysiology, 2025)
Background/Objectives: Urolithiasis is a common disease in Western societies, affecting approximately 10% of the population, and more often men than women. The formation of renal calculi is a complex process, including various compounds and proteins. The aim of this study is to compare differences between the trace element concentrations in male and female renal calculi as well as differences between the trace element concentrations in different stone types. Material and Methods: Renal calculi specimens were obtained during elective nephrolithotripsy procedures. Crystallography of renal calculi was performed using X-ray diffraction; an elemental analysis was performed using Inductively Coupled Plasma–Optical Emission Spectrometry. Statistical analysis was performed to assess the differences in the metal element concentration between men and women. The second part of the analysis measured the differences in the metal element concentration between stones containing calcium phosphate (CaP) and pure calcium oxalate (CaOx) stones. Results: The renal calculi (n = 20) obtained from the male patients had a lower potassium concentration than the calculi (n = 24) from the female patients: 393.4 vs. 792.3 mg/kg, p = 0.007. A comparison of the CaP calculi and CaOx calculi showed a higher zinc concentration (p < 0.001) and potassium concentration (p < 0.001) in the stones containing calcium phosphate. Conclusions: The renal calculi from females had a significantly higher potassium content than those from males. This difference was not correlated with hyperkalemia or the blood potassium levels, suggesting a sex-dependent role of uromodulin in stone formation. The stones containing calcium phosphate exhibited higher zinc and potassium concentrations compared to the pure calcium oxalate stones. The increased presence of zinc and potassium in urine may accelerate the formation of calcium phosphate calculi.